Spousal role and family vacation decision making in India. (2016) - Ashraf, Maria; Khan, Kaleem Mohammad
Family purchase decision making has been an interesting topic of study for marketing researchers, after the ground-breaking work of Davis. Still, there is a lack of serious research in this area in developing countries. This research paper is an empirical study on the role of husband and wives in the purchase decision making process for family vacation of 125 couples in Delhi, India (Metro, Tier I city) and Aligarh, India (Tier II city). The role is examined on the basis of three major purchasing stages and the eight sub-decision stages encountered by the couple when deciding to go on a family vacation. After the analysis, it was found that the role structure for the vacation decision making in India is mainly joint, although, there is a difference between the role structure in Tier I and Tier II cities. In Tier II city like, Aligarh apart from joint decision, husband dominant decision making is also present. This shows that the patriarchal mindset still prevail in smaller cities as compared to a metro.